Ways Of Using Grain in Bread Technology (Open Herald: Periodical of Methodical Research, 2024)
Whole grain wheat bread is not only tasty, but also a healthy product. This paper examines the results of two experimental studies on the use of sprouted grain seeds and crushed wheat grain in bread technology. Grain bread is baked from sprouted and specially crushed wheat grain, which retains almost all the components of the grain. This gives grounds to talk about the exceptional nutritional and biological value of bread